2018
DOI: 10.1177/0194599818801907
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–Associated Oropharyngeal Cancer: Patterns of Nodal Disease

Abstract: Objective To characterize patterns of neck lymph node (LN) metastases in human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma, represented by p16 positivity (p16+OPSCC). Study Design Case series with chart review. Setting Tertiary care center. Subjects and Methods Neck dissection (ND) specimens of nonirradiated p16+OPSCC patients were analyzed for frequencies of clinically evident and occult LNs by neck level. Local, regional, and distant recurrences were reviewed. Results Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
23
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 18 publications
12
23
1
4
Order By: Relevance
“…Importantly, there was potentially a relatively low rate of ECE (23.2%) in this study as compared to other reports in the literature. 27 However, a minority of patients were missing data for ECE; of those with known data, the rate of ECE was 27.8%, similar to some other oropharynx studies. 28,29 It is still possible that there is selection bias to not operate on those with obvious ECE preoperatively; however, we do not believe that such selection bias would affect margin rates.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Importantly, there was potentially a relatively low rate of ECE (23.2%) in this study as compared to other reports in the literature. 27 However, a minority of patients were missing data for ECE; of those with known data, the rate of ECE was 27.8%, similar to some other oropharynx studies. 28,29 It is still possible that there is selection bias to not operate on those with obvious ECE preoperatively; however, we do not believe that such selection bias would affect margin rates.…”
Section: Discussionsupporting
confidence: 76%
“…Both facility factors yielded a P value less than .2. On multivariable regression, patients with LVI were 1.6 times as likely to have [26][27][28][29][30][31][32][33][34][35].93], P < .001). When T4a and T4b were grouped into a single category on multivariable regression, T classification remained a significant predictor of margin status (for T4, OR: 6.94, CI: 3.14-15.30, P < .001), and the rest of the model was unchanged.…”
Section: Factors Associated With Positive Margins On Multivariable mentioning
confidence: 99%
“…Several studies have demonstrated a better quality of life (QOL) in patients who underwent primary surgery for OPSCC . Recent single and dual‐institutional studies show that primary surgical treatment has a comparable OS to primary chemoradiation . Up‐front surgery also has an additional advantage of histopathologic staging …”
Section: Introductionmentioning
confidence: 99%
“…Of three published studies examining the nodal distribution specific to p16 + ve disease, 5-7 one subclassified clinically known and occult nodes. 5 Previous studies examined the distribution of known and occult OPSCC nodal disease irrespective of p16 status, 2,[8][9][10][11] with HPV relatively recently demarcated as a specific disease subtype. 12 Zenga et al examined a large cohort of 324 pN + ve p16 + ve OPSCC patients, but without assessing the neck level distribution of LNs.…”
Section: Discussionmentioning
confidence: 99%